Elaboration of an expert system for sizing, designing and verifying flexible pavements - Bouacha, Nadjet; Belachia, Mouloud (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The use of expert systems in the world of civil engineering, and in particular for roads, has become a necessity for the reason of the particularity, complexity, and diversity of the influencing parameters at the level of the design calculation, the latter of which represents the major source of subsequent degradation. This system consists of proposing a tool for helping the user firstly to size the body of the roadway, with several analytical methods and models (Pre-project, Boussinesq, Westgaard, and Burmister), and secondly, to offer different design possibilities (thickness and type of the material) that make up the layers.
Keywords: expert systems; sizing; flexible pavement; database; constraints; displacements; systemy eksperckie; dobór; nawierzchnia elastyczna; baza danych; ograniczenia; przemieszczenia